2005
DOI: 10.1021/jf047798g
|View full text |Cite
|
Sign up to set email alerts
|

Masked Mycotoxins:  Determination of a Deoxynivalenol Glucoside in Artificially and Naturally Contaminated Wheat by Liquid Chromatography−Tandem Mass Spectrometry

Abstract: Conjugated mycotoxins, in which the toxin is usually bound to a more polar substance like glucose, are referred to as masked mycotoxins, as these substances escape routine detection methods but can release their toxic precursors after hydrolysis. This is the first report on the natural occurrence of a glucoside of deoxynivalenol (DON) in Fusarium-infected wheat and maize. To obtain appropriate standards, we chemically synthesized deoxynivalenol-3-beta-D-glucopyranoside (DON-3-glucoside) and deoxynivalenol-15-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
218
1
6

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 344 publications
(233 citation statements)
references
References 14 publications
8
218
1
6
Order By: Relevance
“…Metabolism by the host plant generally aims at detoxification of these compounds which is often accomplished by attachment of hydrophilic groups, thus increasing their solubility in water (Engelhardt et al 1999;Karlovsky 1999). In this manner, DON is converted to DON-3-glucopyranoside (D3G) (Sewald et al 1992;Berthiller et al 2005), and ZON can be altered to ZON-4 glucopyranoside (Z4G) (Engelhardt et al 1988) by plants.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolism by the host plant generally aims at detoxification of these compounds which is often accomplished by attachment of hydrophilic groups, thus increasing their solubility in water (Engelhardt et al 1999;Karlovsky 1999). In this manner, DON is converted to DON-3-glucopyranoside (D3G) (Sewald et al 1992;Berthiller et al 2005), and ZON can be altered to ZON-4 glucopyranoside (Z4G) (Engelhardt et al 1988) by plants.…”
Section: Introductionmentioning
confidence: 99%
“…Maul et al (2012) determined 30% reduction of DON in steeping process. Berthiller et al (2005) detected 1:3 ratio of D3G to DON in wheat kernels. From our results, it was concluded that the ratio could be higher in harvested kernels, even 1:1 (Figure 2a, barley).…”
Section: Resultsmentioning
confidence: 93%
“…Conjugated forms arise from DON as detoxification products decreasing toxicity of DON in plants (Berthiller et al 2005) or they are intermediate products on DON biosynthetic pathway in Fusarium (McCormick et al 2011), as in case of ADONs. It is evident that testing of primary produced DON in plants is insufficient for evaluation of total content of Fusarium mycotoxins, both in non-processed raw material and processed products.…”
mentioning
confidence: 99%
“…Modified mycotoxins represent another emerging topic. Plant metabolites have been identified so far for DON, NIV, fusarenon-X, T-2 toxin, HT-2 toxin, ZEA, ochratoxin A (OTA), destruxins, fusaric acid, and modified fumonisins have been found, especially in wheat and other cereal commodities [41][42][43][44][45][46]. The acetylated derivatives of DON, 3-ADON, and 15-ADON are frequently detected in DON-contaminated grains [47].…”
Section: Mycotoxinsmentioning
confidence: 99%